TANGGUNG JAWAB PEMILIK KOS TERHADAP KEHILANGAN BARANG PENYEWA DI SEPAKAT DUA KOTA PONTIANAK - NIM. A1011211157, RESKI MONANDAR (Jurnal Fatwa Hukum, 2025)
Abstract  The owner of the boarding house as the business actor of the lodging house is obliged to maintain the environment of his place of business so that the tenants feel safe and comfortable, but in reality there are still some boarding houses whose security is not adequate so that there is a loss of tenant goods, and if there is a loss of tenant goods, the owner of the boarding house as the manager of the lodging house is charged with the responsibility to compensate for the loss because the tenant's goods are forced entrusted goods as stated in article 1709 and the owner of the boarding house is obliged to compensate for the loss of tenant goods as stated in article 1710 of the Civil Code. Based on the results of the author's research, the boarding house owner has not been responsible for compensating for the loss of the tenant's goods, the factor that causes the boarding house owner to not be responsible for compensating for the loss is because the boarding house owner does not know the provisions of article 1709 and article 1710 of the Civil Code so that they feel that the tenant's goods are not the responsibility of the boarding house owner and the legal consequences for the boarding house owner are that there is no result because the tenants have never made any legal efforts including claiming compensation against the boarding house owner.  Keywords: Landlord; Tenant; Goods; Lodging HouseAbstrak  Pemilik kos sebagai pelaku usaha rumah penginapan wajib menjaga lingkungan tempat usahanya agar para penyewa merasa aman dan nyaman, namun pada kenyataannya masih dijumpai beberapa kos yang keamanannya belum memadai sehingga terjadi kehilangan barang penyewa, dan jika terjadi kehilangan barang penyewa maka pemilik kos selaku pengelola rumah penginapan dibebankan tanggung jawab mengganti kerugian karena barang penyewa merupakan barang titipan terpaksa hal tersebut tertuang di dalam pasal 1709 dan pemilik kos wajib mengganti kerugian terhadap barang penyewa yang hilang hal tersebut tertuang di dalam pasal 1710 KUH Perdata. Berdasarkan hasil penelitian penulis pemilik kos belum bertanggung jawab mengganti kerugian terhadap kehilangan barang penyewa, faktor yang menyebabkan pemilik kos belum bertanggung jawab mengganti kerugian karena pemilik kos tidak mengetahui ketentuan pasal 1709 dan pasal 1710 KUH Perdata sehingga mereka merasa barang penyewa bukan tanggung jawab pemilik kos dan akibat hukum bagi pemilik kos adalah tidak berakibat apapun karena para penyewa belum pernah melakukan upaya hukum apapun termasuk menuntut ganti rugi terhadap pemilik kos.  Kata Kunci: Pemilik, Penyewa, Barang, Rumah Penginapan